Ta’śīr Țarīqah Prediction Guide ‘alā Natāij al-Ikhtibār litullāb Madrasah al-Khairāt al-Muțawwasițah al-Islāmiyah bi Gorontalo - Ca Manggalupang, Marsanda; Hairuddin, Hairuddin; Arsyad, Berti (Yayasan Daarul Qimmah Gorontalo, 2024)
This study aims to describe the influence of the prediction guide method on the learning outcomes of grade VII students of MTs Al-Khairaat, Gorontalo City. The sample in this study consisted of two experimental groups of 20 students and a control group of 13 students. The experimental group is a group that carries out Arabic language learning using the Prediction Guide Method, while the control group is a group that carries out Arabic language learning without using the Prediction Guide Method. The instrument used is a test instrument (objective question test). Based on the results of the hypothesis test, the significance value or Asymp. Sig. (2-tailed) is 0.000, which is smaller than 0.05, which shows that the use of the Prediction Guide method in learning Arabic has a positive effect on the learning outcomes of grade VII students of MTs Al-Khairaat Gorontalo City.